Initial Conditions and the Outcome of Economic Reform - Kaltani, Linda (2012)
This paper studies how initial conditions affect the outcome of reform using the case of trade liberalization as an example. The paper illustrates empirically and theoretically the seemingly paradoxical case of larger impact of reform when initial conditions are poorer.